Integrating Media Literacy in Da'wah: Effective Communication Strategies for Religious Counselors in Preventing Early Marriage - Sampurna, Ahmad; Asna, Atikah; Mohammadi, Ghasem (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2025)
Early marriage remains a serious issue in West Nias Regency, particularly affecting young girls. Religious instructors, as respected community figures, are seen as vital agents in preventing early marriage through education based on religious values. However, challenges such as limited digital access, low media proficiency, and generational communication gaps reduce their effectiveness, especially in reaching youth influenced by social media. This study explores how media literacy can enhance religious instructors' role in early marriage prevention. Using a Community-Based Research (CBR) approach and qualitative methods, the study engaged 28 participants—including instructors, community leaders, and youth—through interviews, FGDs, and observations. Results show that instructors trained in basic digital skills used tools like WhatsApp, Facebook, and video editing apps to create religious-themed videos and interactive content. These methods significantly improved youth engagement. One instructor noted, “After learning how to use videos and infographics, more teenagers listened and asked questions.” The study concludes that media literacy is a key communication strategy, not just a technical skill. It enables instructors to connect more effectively with younger audiences and address sensitive topics like early marriage. Two key recommendations are: (1) establish ongoing, tailored media literacy training for religious instructors, and (2) build partnerships with schools and youth organizations to develop collaborative digital campaigns. These strategies can empower religious instructors to become more dynamic, youth-friendly communicators and help reduce early marriage in West Nias.